Correlation of Hormonal Profile and Lipid Levels with Female Adult Acne in a Tertiary Care Center of Nepal - Shrestha, Smriti (Journal of Nepal Health Research Council, 2018)
Background: Acne beyond 25 years of age is frequently associated with hormonal derangement in women. Hormonal association provides the impetus for hormonal therapy as well as underpins the need for blood investigations in this population. Hence, we aim to estimate the presence of hormonal derangement and lipid alteration in female adult acne. Methods: A prospective, observational study was conducted in Dhulikhel Hospital from July 2015 to February 2016. Females older than 25 years with acne were taken in the study after informed consent. Total 100 patients were enrolled after sample size estimation. Hormonal paneland lipid profile were measured. Hormones tested were androgens, C-peptide and thyroid stimulating hormone.Data analysis was done with SPSS-23. Bivariate analysis was done by chi-square test for categorical data. Results: In this study, majority of patients were younger than 30 years (70.5%) and perioral area most commonly involved. Hormonal alteration was seen in 37.2% patients, among which17.9% had hyperandrogenism, 15.4% had abnormal thyroid level and 10.3% had high C-peptides respectively. Lipid profile was altered in 15.4% patients. Hormonal alteration had significant association with irregular menstruation (P<0.05) but not acne severity. Conclusions: We observed hormonal alteration frequently in females with adult acne, which comprised of various hormonal parameters including hyperandrogenism.Hormonal alteration reflects deranged metabolic milieu and we suggest that wide hormonal panel should be done in female adult acne. Relationship of hormones with menstrual irregularity but not with acne severity, suggest that clinical symptoms should lead hormonal investigations in all grades of acne. Keywords: Acne; adult; hormones; lipid; thyroid.